ANALISIS PEMBENTUKAN CITRA PARIWISATA GOA KREO TERHADAP USAHA MIKRO DAN KECIL MASYARAKAT KANDRI SEMARANG - Fallen Oktafian; Ari Pradhanawati; Wahyu Hidayat (Universitas Diponegoro, 2016)
This research is motivated by the changes of Goa Kreo as a Vacational Destination that located in Kandri Village Gunungpati Semarang. The changes it self including Vacational Branding about the contruction of Jatibarang Dam.The purpose of this study is to determine any possible factors which happened On vacational cluster of Goa Kreo itself, Society and also The People of Small-Mid Enterprises. The Brand movement was about Economic and socio cultural of the Society.The results of this study indicate that the Changes of Branding Campaign on Goa Kreo was also effected the Society especially for Small Middle Enterprises.Suggestions can be delivered is preferably about the vacational management that involved multi effort of the People.